Internship Experience: The MMMAPS, the WorST, and the Interns - Quinto, Joseph Bello; Diase, Frances Mae Gacoscos (Universitas Negeri Yogyakarta, 2024)
Undergraduate internship is the first access of students in the world of work that is why it is worth investigating what student-interns' experiences are. In this regard, the researchers delved into the alignment of the internship tasks given to Bachelor of Arts in Communication seniors in one prime state university toward their career trajectories anchored on CMO number 35, series of 2017 as required by the Commission on Higher Education in the Philippines, and the hurdles that they experienced in their internship deployment. By employing Qualitative Content Analysis of diary entries of thirty-two (32) interns from March 14, 2022, to May 13, 2022, in thirty-one (31) host offices, the following themes surfaced. The career trajectories are expressed in